TEXNOLOGIYA TA’LIMI O‘QITUVCHILARIGA QO‘YILADIGAN ZAMONAVIY TALABLAR - Kuttibekova, G.T. (SCIENCE and SOCIETY, 2023)
Scientific-methodical work on the development of information-receiving competence of future teachers consists in ensuring the integration of general professional subjects and information-related subjects, creating integrative programs and training manuals.
Keywords: school; educational subjects; labor education; socio-economic; scientific; theoretical and practical; material - technical; social; knowledge; skill; qualification; student